Principles of gene manipulation and genomics - Primrose, S. B.; Twyman, Richard M. (Blackwell Publishing, 2006)
"The increasing integration between gene manipulation and genomics is embraced in this book, Principles of Gene Manipulation and Genomics, which brings together for the first time the subjects covered by the best-selling books, Principles of Gene Manipulation and Principles of Genomic Analysis and Genomics. This new text has been comprehensively revived, updated, and rewritten to encompass within one volume, basic